An Inhibitory Anti-factor IX Antibody Effectively Reduces Thrombus Formation in a Rat Model of Venous Thrombosis - Feuerstein, Giora Z.; Toomey, John R.; Valocik, Richard; Koster, Paul; Patel, Arun; Blackburn, Michael N. (Thrombosis and Haemostasis, 1999)
An inhibitory anti-factor IX/IXa antibody (BC2) has been investigated as an anti-thrombotic agent in a rat venous thrombosis model. The treatment of rats post-injury with a single bolus dose of BC2 (3mg/kg, iv.) resulted in an ~4 fold reduction in venous thrombus mass (P = 0.043). This efficacy was matched by a minimal (<2.5 fold) prolongation of the aPTT and had no effect on the prothrombin time (PT). Heparin by comparison, given as a bolus followed by continuous infusion, at doses comparable in efficacy at reducing thrombus formation, prolonged the aPTT >50 fold. These results demonstrate that the anti-factor IX/IXa antibody (BC2), when compared to heparin, can effectively reduce venous thrombosis with less disruptive consequences on blood clotting.
Keywords: Antibodies; anticoagulants; thrombosis; factor IX